Negotiating the Great Recession: How Teacher Collective Bargaining Outcomes Change in Times of Financial Duress - Katharine O. Strunk; Bradley D. Marianno (SAGE Publishing, 2019)
This article examines how teacher collective bargaining agreements (CBAs), teacher salaries, and class sizes changed during the Great Recession. Using a district-level data set of California teacher CBAs that includes measures of subarea contract strength and salaries from 2005-2006 and 2011-2012 tied to district-level longitudinal data, we estimate difference-in-difference models to examine bargaining outcomes for districts that should have been more or less fiscally constrained. We find that unions and administrators change critical elements of CBAs and district policy during times of fiscal duress. This includes increasing class sizes, reducing instructional time, and lowering base salaries to relieve financial pressures and negotiating increased protections for teachers in areas with less direct financial implications, including grievance procedures and nonteaching duties.